ANALYSIS OF RECLAIMED WATER POTENTIAL IN THE RESIDENTIAL SECTOR AND ITS TREATMENT TECHNOLOGY ALTERNATIVES IN THE URBAN AREA OF DKI JAKARTA - Rahmayanti Prihadi, Putri
DKI Jakarta is an area with the highest population density in Indonesia. One of the problems arising from this condition is the increasing demand for clean water. Unfortunately, the demand for clean water is not proportional to its availability. This is due to the declining quality of water sources caused by pollution and excessive groundwater exploitation. One alternative to address this issue is to implement the use of reclaimed water as a water source for the community. Reclaimed water refers to the wastewater from consumption activities, which is then treated and reused for various purposes, such as potable and non-potable water supplies. Based on the analysis of data from 44 centralized wastewater management systems and 126 decentralized wastewater management systems, the potential for reclaimed water in the residential sector in 2022 - 2023 in urban areas of DKI Jakarta ranges from 380 - 3,300 m3/day for centralized systems and 22.68 m3 /day for decentralized systems. Furthermore, the suitable technologies for reclaimed water treatment technologies from a centralized system are sand filters, carbon filters, microfiltration, reverse osmosis, and chlorination. Meanwhile, the suitable technologies for decentralized systems are aerated treatment systems, sand filters, carbon filters, and chlorination.